Quasi-Consensus of Time-Varying Multi-Agent Systems with External Inputs under Deception Attacks - Zeng, Zixian; Peng, Shiguo; Feng, Wandian (Entropy (Basel, Switzerland), 2022)
The quasi-consensus of a class of nonlinear time-varying multi-agent systems suffering from both external inputs and deception attacks is studied in this paper. This is different from a time-varying matrix, which is assumed to be bounded; further reasonable assumptions are supposed. In addition, impulsive deception attacks modeled with Bernoulli variables are considered. Sufficient conditions to achieve quasi-consensus are given, and the upper bounds of the error state related to the deception attacks is derived. Finally, a numerical simulation example is provided to show the validity of the obtained results.